Return of Fertility After Discontinuation of Contraception According Type of Contraception, Duration of Use, Age and BMI: Kembalinya Kesuburan Pasca Penghentian Alat Kontrasepsi Berdasarkan Jenis Kontrasepsi, Lama Pemakaian, Usia dan IMT - Quinita M. J. Noronha; Hafi Nurinasari; Uki R. Budihastuti; Darto (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective : To determine the relationship between the type of contraception, duration of use, BMI, and age on the return of fertility.Methods : This was an analytic observational study with a cross-sectional design. The subjects in this study was 123 multigravida mothers who had met the inclusion criteria, namely with a history of regular intercourse and the exclusion criteria in this study were multigravida mothers with a history of abortion and failure of the family planning method. Data were collected by direct interviews and medical record data. Data were analyzed using Chi-square test and Logistic Regression test.Results: The results of the Chi-square analysis showed a relationship between the type of contraception (p=0.001;OR=1.29) and age (p=0.031;OR=4.69) with the return of fertility. However, there was no correlation between the duration of use (p=0.964;OR=0.97) and BMI (p=0.246;OR=0.50) with the return of fertility. In the logistic regression test, there was no partial effect of the type of contraception (p=0.997;OR=0.22) and age (p=0.058;OR=0.01).Conclusion : Based on the results of the analysis, it can be concluded that there is a relationship between the type of contraception and age with the return of fertility after family planning, where non-hormonal contraceptives and <30 years of age return to fertility faster, namely <1 year, but there is no relationship between duration of use and BMI with the return of fertility after family planning.Keywords: contraception, family planning, fertility. Abstrak Tujuan: Mengetahui hubungan jenis kontrasepsi, lama pemakaian, IMT, dan usia terhadap kembalinya kesuburan.Metode: Penelitian ini merupakan penelitian observasional analitik dengan desain potong lintang. Subjek penelitian ini adalah ibu multigravida yang telah memenuhi kriteria inklusi yaitu dengan riwayat senggama teratur dan bersedia menjadi responden serta kriteria ekslusi dalam penelitian ini adalah ibu multigravida dengan riwayat abortus dan kegagalan metode KB. Besar subjek dalam penelitian ini sebanyak 123 orang. Pengambilan data dilakukan dengan wawancara langsung dan melihat data rekam medis. Analisis data dilakukan uji statistik Chi-square dan uji Regresi Logistik.Hasil : Hasil analisis dengan Chi-square, menunjukan adanya hubungan jenis kontrasepsi (p = 0,001; OR = 1,29) dan usia (p=0,031; OR = 4,69) dengan kembalinya kesuburan. Namun, tidak terdapat hubungan lama pemakaian (p= 0,964; OR =0,97) dan IMT (p= 0,246; OR =0,50) dengan kembalinya kesuburan. Pada uji regresi logistik tidak terdapat pengaruh parsial dari jenis kontrasepsi (p=0,997; OR =0,22) dan usia (p=0,058; OR=0,01).Kesimpulan : Berdasarkan hasil analisis yang dilakukan dapat disimpulkan terdapat hubungan jenis kontrasepsi dan usia dengan kembalinya kesuburan pasca KB, dimana pada jenis kontrasepsi non hormonal dan usia < 30 tahun lebih cepat kembali subur yaitu < 1 tahun, namun tidak terdapat hubungan lama pemakaian dan dengan kembalinya kesuburan pasca KB.Kata kunci: keluarga berencana, kesuburan kontrasepsi.